The Alzheimer’s Disease “non-amyloidogenic” p3 peptide revisited: a case for Amyloid-α - Kuhn, Ariel J. (ACS Chem Neurosci, 2020)
Amyloid-β (Aβ) is an intrinsically disordered peptide thought to play an important role in Alzheimer’s Disease. It has been the target of most AD therapeutic efforts, which have repeatedly failed in clinical trials. A more predominant peptidic fragment, formed through alternative processing of the Amyloid Precursor Protein, is the p3 peptide. p3 has received little attention, which is possibly due to the prevailing view in the AD field that it is “non-amyloidogenic”. By probing the self-assembly of this peptide, we found that p3 aggregates to form oligomers and fibrils, and when compared with Aβ, displays enhanced aggregation rates. Our findings highlight the solubilizing effect of the N-terminus of Aβ, and the favorable formation of structures formed through C-terminal hydrophobic peptide interfaces. Our findings suggest a reevaluation of the current therapeutic approaches targeting only the β-secretase pathway of AD, given that the α- secretase pathway is also amyloidogenic.